THE INFLUENCE OF COMPETENCE AND INTERNAL COMMUNICATION ON LECTURER PERFORMANCE AT PRIVATE UNIVERSITIES IN MEDAN CITY - Indah Sari Liza Lubis (Journal of Information Systems Management and Digital Business, 2024)
The tight competition among private universities in Medan City, especially at the postgraduate level, leads to an increase in quality based on the quality of lecturers. Lecturer performance is critical to improve the quality of graduates. Several variables affect teacher performance. This study focuses on lecturers who teach master's and doctoral programs at private universities in Medan City. The number of respondents in the survey was 255 lecturers. The structured equation model was used to process the data of this study. The results of this study indicate that the variables of competence and job satisfaction significantly affect lecturer satisfaction; the variable of job satisfaction mediates the effect of competence on lecturer performance. Job satisfaction is the most dominant factor affecting teacher performance, while internal communication does not significantly affect teacher performance.